2012
DOI: 10.4067/s0718-16202012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality and carcass characteristics of Merino Precoce suckling lambs raised under confinement in the Mediterranean semi-humid dryland of Central Chile

Abstract: Twenty-eight Merino Precoce suckling lambs raised under confinement in the Mediterranean semi-humid dryland of Central Chile were studied to evaluate meat quality and major carcass characteristics. Animals were grouped by slaughter weight (10 and 15 kg) and sex (7 males and 7 females in each weight group). The average commercial and true dressing percentages were 53 and 55%, the average ribeye area was 11.7 cm 2 , and the average dorsal fat thickness was 1.5 mm. The largest retail yields were those of the leg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The desirable pH ranges in sheep meat are between 5.4 and 5.8 [57]; the pH values obtained in this study were found within this range. Perez et al [58] reported 1.68% EE and 1.2% ash in Merino lambs, similar in EE but lower in ash, compared to the present investigation. However, Ayele et al [59] reported ash values between 4.08 and 6.15%, closer to those observed in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…The desirable pH ranges in sheep meat are between 5.4 and 5.8 [57]; the pH values obtained in this study were found within this range. Perez et al [58] reported 1.68% EE and 1.2% ash in Merino lambs, similar in EE but lower in ash, compared to the present investigation. However, Ayele et al [59] reported ash values between 4.08 and 6.15%, closer to those observed in the present study.…”
Section: Discussionsupporting
confidence: 77%